Implementation of Fuzzy Mamdani to Detect the Suitability of Drinking Water - Susilawati, Susilawati; Nugraha, Riki Tri (Peneliti.net, 2024)
Water is a liquid substance has no taste, smell and color. The constituent elements, there are hydrogen and oxygen with the chemical formula H2O. Because water has properties that can be used for almost anything, water is the most important substance for all forms of life (plants, animals and humans). Drinking water consumed by the public must meet quality and quantity requirements, the quality requirements of which are contained in Minister of Health Regulation no. 146 of 1990 concerning water quality requirements and supervision. The aim of this research is to design a detection tool with Arduino Mega that can measure the suitability of drinking water using a water pH sensor and TDS sensor. This methodology was prepared according needs for software and hardware, namely identification of needs, design, implementation and testing. The testing stage was divided into two, namely testing carried out on the water pH sensor with an average accuracy of 95.63% and the TDS sensor with an accuracy of 97.28%. Testing of the accuracy of the Mamdani system's fuzzy logic calculation method against manual calculations showed an average accuracy of 90.96%.